Hubungan antara kadar pulangan nominal dengan permintaan deposit sistem perbankan islam di Malaysia - Zulkefly Abdul Karim; Aminudin Mokhtar; Mohd Azlan Shah Zaidi (Penerbit Universiti Kebangsaan Malaysia, 2004)
The main objective of this study is to examine the influence of the rates of return of deposit on demand for deposit in Islamic Banking System (SPI) which comprises of commercial banks, finance companies and merchant banks which provide islamic banking scheme. Early finding of Chow test showed that there exists a structural break in the sample period of deposit demand function for each of the institution and the SPI as a whole. As a result, the analysis is done on two sample periods which are from March 1994 to June 1997 (sample 1) and July 1997 to November 2002 (sample 2). Results of causality tests from vector error correction model for sample 1, show that the change in the rates of return for investment deposit (KPDP) causes the change in the demand for investment deposit (DP) for the commercial banks, the finance companies and the SPI as a whole. Furthermore, there is also a bilateral causality between the change in the rates of return for saving deposit (KPDS) and the change in the demand for saving deposit (DS) for the commercial banks. The results are different for sample 2, whereby bilateral causality exists between the change in KPDP and the change in DP for the commercial banks as well as for the SPI as a whole. For the merchant banks, the change in DP has significant influence on the change in KPDP either in the long run or the short run. Compared to the results in sample 1, the change in KPDS in sample 2 has significant influence on the change in DS for each of the institution and for the SPI as a whole. Thus, the findings reveal that the rates of return on deposit play a vital role in influencing the behavior of economic units to demand for deposit in the SPI.